一、脱式计算                                                                               
77-46+32      65-38+26          79+19-56      69-(39-23)    (2+7)×8       
=            =                =            =              =
=            =                =            =              =
58-34)÷8       84-27+16=      4+27-16    99+25-24)    6×(2+6)     
=              =                =          =              =
=              =                =          =              =
————————————————————————————————————————————                 
二、脱式计算                                                                               
3×9×3          93+23+94      4×6+7          20÷4+5        6×8+5 
=            =                =            =              =
=            =                =            =              =
(75-18)×7   77-76+32      61-38+26        9×6+4      10+5×4       
=              =                =              =              =
=              =                =              =              =                         
三、脱式计算                                                                               
77-76+32        61-38+26          79+19-16    18-36+27       30+(23-29)     
=            =                =            =              =
=            =                =            =              =
73-23-4          93-(39-23)      71-25-24)    87-27+16    99-46+32     
=              =                =          =              =
=              =                =          =              =                           
四、脱式计算                                                                               
59-36+29       94-29+96        30-(23-29)    93-23+94        71-25-24   
=            =                =            =              =
=            =                =            =              =
33-(39-23)   99-25-24)    99-96+32        69-39+26        87-27+16       
=              =              =              =              =
=              =              =                =              = 
五、脱式计算                                                                               
99+99-96        6×2+7      7×(45÷5)    19+9×6         16÷2×7     
=            =                =            =              =
=            =                =            =              =
(19+2)÷3  (36÷4)+27      32÷4+16    29-4×2       42÷6×7     
=              =                =          =              =
=              =                =          =              =
—————————————————————————————————————————————
六、脱式计算                                                                               
30-(23+29)        3+23+94      93-(39-23)     99-99-29)  99-36+29     
=            =                =            =              =
=            =                =            =              =
99-29+96        55-46+22      65-28+26      58+18-56        58-26+25  
=              =            =              =              =
=              =            =              =              =
七、脱式计算                                                                               
84-25+16     4+25-1            82+22+84     68-(28-22)        18-26+25     
=            =                =            =              =
=            =                =            =              =
88+25-24    55-56+22        61-28+26      58+18-16       85-25+16   
=              =                =          =              =
=              =                =          =              =
—————————————————————————————————————————————                       
八、脱式计算                                                                               
82-(28-22)        51-25-24    88-46+22    65-28+26        20+(22-28)       
=            =                =            =              =
=            =                =            =              =
88+88-56        58-26+28         84-28+86        20-(42-28)   52-22-4     
=              =            =              =              =
=              =            =              =              =           

更多推荐

计算,脱式